2009
DOI: 10.1038/nsmb.1739
|View full text |Cite
|
Sign up to set email alerts
|

Strong cooperativity between subunits in voltage-gated proton channels

Abstract: Voltage-activated proton (HV) channels are essential components in the innate immune response. HV channels are dimeric proteins with one proton permeation pathway per subunit. It is not known how HV channels are activated by voltage and whether there is any cooperativity between subunits during voltage activation. Using cysteine accessibility measurements and voltage clamp fluorometry, we show data that are consistent with that the fourth transmembrane segment S4 functions as the voltage sensor in HV channels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

36
328
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(365 citation statements)
references
References 41 publications
36
328
1
Order By: Relevance
“…It has been proposed that the gating movement of one monomeric channel subunit affects the gating of the other subunit within the dimeric unit [16][17][18] . We observed, in this study, dimerization by the coiledcoil assembly affected the thermosensitive gating.…”
Section: Coiled-coil Assembly Domain Of Mhv1/vsop and Its Structurementioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that the gating movement of one monomeric channel subunit affects the gating of the other subunit within the dimeric unit [16][17][18] . We observed, in this study, dimerization by the coiledcoil assembly affected the thermosensitive gating.…”
Section: Coiled-coil Assembly Domain Of Mhv1/vsop and Its Structurementioning
confidence: 99%
“…One characteristic derived from the dimer assembly in the Hv channel is the cooperative channel gating-that is, the gating movement of one monomeric channel subunit affects the gating of the other subunit within the dimeric unit [16][17][18] . However, it remains unclear through which part of the channel the conformational change is transmitted from one subunit to the other during channel gating.…”
mentioning
confidence: 99%
“…These structural models will be essential for future investigations of this channel and the development of new pharmacological blockers. (15,16). Accessibility experiments of cysteines introduced into S4 of Hv1 channels suggest that S4 functions as the voltage sensor and that there is an outward movement of S4 upon membrane depolarization (15,16).…”
mentioning
confidence: 99%
“…(15,16). Accessibility experiments of cysteines introduced into S4 of Hv1 channels suggest that S4 functions as the voltage sensor and that there is an outward movement of S4 upon membrane depolarization (15,16). The three positively charged residues contribute most, if not all, of the gating charges in Hv1 channels (15,16).…”
mentioning
confidence: 99%
“…Multiple functions were proposed for proton channels, but these remained speculative until the cloning of the Hv1 protein by two separate laboratories (Ramsey et al, 2006;Sasaki et al, 2006) and the generation of Hv1 knockout mice offered the possibility to test the physiological role of proton channels. Structure-function studies revealed that Hv1 channels are dimers that gate cooperatively (Gonzalez et al, 2010;Musset et al, 2010;Tombola et al, 2010), with each monomer containing a separate conduction pathway and voltage sensor (Koch et al, 2008;Lee et al, 2008;Tombola et al, 2008). Hv1 channels are perfectly selective for protons and are activated by depolarizing voltages and by intracellular acidification, a combination that ensures that the channels only open in conditions that favor proton extrusion from cells.…”
mentioning
confidence: 99%